Standardizing Compound Test For Measuring Scoring Accuracy From Quick Motor Response - Abedul Hussein, Mohammed; Nabeel, Bader (Journal of Physical Education, 2018)
Standardizing Compound Test For Measuring Scoring Accuracy From Quick Motor ResponseThe importance of the research lies in including up to date devices for measuring and testing motor response speed and the accuracy of scoring by using Audio device that gives orders and commands about the test as well as calculate time. The problem of the research was the weakness in measuring time of motor response. The research aimed at adjusting the audio device for measuring motor response time and combining it with the accuracy of performing scoring in soccer for advance players. The researcher used the descriptive method. The subjects were (54) players from three clubs. The data was collected and treated using proper statistical operations to conclude test criteria for motor response time and scoring accuracy using audio stimuli. Finally the researchers recommended using this test for measuring motor response time in soccer primer league, making similar studies for female players and using devices for measuring other abilities and traits.